2017
DOI: 10.1001/jama.2016.21048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Integrated Pest Management Intervention on Asthma Symptoms Among Mouse-Sensitized Children and Adolescents With Asthma

Abstract: IMPORTANCE Professionally delivered integrated pest management (IPM) interventions can reduce home mouse allergen concentrations, but whether they reduce asthma morbidity among mouse-sensitized and exposed children and adolescents is unknown.OBJECTIVE To determine the effect of an IPM intervention on asthma morbidity among mouse-sensitized and exposed children and adolescents with asthma.DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial conducted in Baltimore, Maryland, and Boston, Massachusetts. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 16 publications
4
86
0
Order By: Relevance
“…The intervention procedures will be those that were used in the Boston pilot home intervention study,[14] and the Inner-City Asthma Study (ICAS) Study,[11] and the NIAID funded Mouse Allergen Asthma Intervention Trial (MAAIT). [15] The school-specific IPM will focus on surrounding areas that feed into the classroom and harbor infestation by food and water sources (i.e. cafeteria).…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention procedures will be those that were used in the Boston pilot home intervention study,[14] and the Inner-City Asthma Study (ICAS) Study,[11] and the NIAID funded Mouse Allergen Asthma Intervention Trial (MAAIT). [15] The school-specific IPM will focus on surrounding areas that feed into the classroom and harbor infestation by food and water sources (i.e. cafeteria).…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Our methods are modeled off of successful intervention work in Boston homes[14] which led to our NIAID funded home based study Mouse Allergen Asthma Intervention Trial. [15] This trial utilized successful strategies targeted to the bedroom, inspection targeted in surrounding areas, and in the kitchen. Our school-based study will focus on the primary exposure school room of interest, the child’s classroom, surrounding support areas, and the cafeteria.…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, nonclinical measures such as missed school days and reduced sleep disruption are suggestive of a beneficial impact on asthma morbidity, although this has not been substantiated through clinical measures. Beyond these steps, any benefit to asthma morbidity associated with more intensive interventions, such as a professionally delivered, integrated pest management program delivered in combination with this education, has not been proven [183]. …”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%
“…Interestingly, some studies suggest that interventions that target only a single allergen, or even a single location, for example the bedroom, can be efficacious [183, 190, 198]. Although studies have reported mixed findings [53•, 123, 181, 197], they highlight the need to revisit the widely-debated issue of the efficacy of single- versus multifaceted interventions and to improve behavioral compliance in a sustainable way.…”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%